2015
DOI: 10.18632/oncotarget.4742
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 pathway regulates lung-derived brain metastasis initiating cell capacity through miR-21 activation

Abstract: Brain metastases (BM) represent the most common tumor to affect the adult central nervous system. Despite the increasing incidence of BM, likely due to consistently improving treatment of primary cancers, BM remain severely understudied. In this study, we utilized patient-derived stem cell lines from lung-to-brain metastases to examine the regulatory role of STAT3 in brain metastasis initiating cells (BMICs). Annotation of our previously described BMIC regulatory genes with protein-protein interaction network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…Furthermore, stratified analysis of BMs showed that, compared with EGFR wild type, EGFR mutations group had a significant higher incidence of subsequent BMs and a trend of increasing the incidence of initial BMs. The mechanisms behind it may be as follows: EGFR activated MET through mitogen activated protein kinases (MAPK) to promote BMs in NSCLC (43); moreover, EGFR activated the STAT3 via elevating expression of interleukin-6 (IL-6) in lung cancer which results in the up-regulation of incidence of BMs (44,45). Whereas, the inconsistent conclusions between the initial and subsequent BMs were possibly due to the intervention of EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stratified analysis of BMs showed that, compared with EGFR wild type, EGFR mutations group had a significant higher incidence of subsequent BMs and a trend of increasing the incidence of initial BMs. The mechanisms behind it may be as follows: EGFR activated MET through mitogen activated protein kinases (MAPK) to promote BMs in NSCLC (43); moreover, EGFR activated the STAT3 via elevating expression of interleukin-6 (IL-6) in lung cancer which results in the up-regulation of incidence of BMs (44,45). Whereas, the inconsistent conclusions between the initial and subsequent BMs were possibly due to the intervention of EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Nadiya et al have found that the miR-21 expression was significantly increased in the cerebrospinal fluid of patients with glioblastoma and BM of breast and lung cancers, indicating that miR-21 may be a potential biomarker for both glioblastoma and BM 25. Singh et al have demonstrated that miR-21 is overexpressed in lung cancer patients and is associated with a poor prognosis; meanwhile, Singh et al suggested that miR-21 might regulate the metastatic behavior of BM initiating cells by targeting STAT3, and hence blocking the STAT3−miR-21 pathway could be a novel therapeutic treatment in patients with lung-to-brain metastasis 26. A previous study performed by Zhang et al has demonstrated that NSCLC patients with distal metastasis had higher miR-21 expression than those without distal metastasis, and the overexpression of miR-21 may be involved in the metastasis and invasion of tumor cells 18…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutation in lung cancer was often found to result in the activation of signal transducers and activators of transcription 3 (STAT3) [34,35]. Recently, Singh et al [36] identified STAT3 as an upregulator of lung-to-brain metastases. According to this study, the activation of the STAT3 signal pathway by EGFR mutation may contribute to increased BM risk for patients with EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%